GESTAÇÃO E VIA DE PARTO: INFLUÊNCIA SOBRE A PELVE E ASSOALHO PÉLVICO DE PRIMÍPARAS - Severo, Alexandre Rodrigues (2018)
The gestational period can represent a special moment in the woman's life, in which she experiences anatomical, physiological, biochemical, social and cultural changes and readaptations, as well as a process of preparation for changes and new responsibilities. However, changes caused by cesarean delivery or normal delivery may lead to tissue-level repercussions in the pelvic floor and impairment of pelvic mobility in women. Thus, Manuscript 1 aimed to perform a search in the literature on articles that deal with the relationship between natural delivery and cesarean delivery with urinary incontinence, fecal incontinence, strength and mobility of the pelvic floor. Articles published and indexed in the LILACS, Medline, PubMed, Scopus and PEDro databases were evaluated in the last ten years. Four articles were found. Two of them present a relationship between the type of delivery and the probable predisposition to the development of changes such as urinary and fecal incontinence. The other two studies report the predisposition to poor counseling on the contraction performed during the time of delivery. It is concluded that the articles presented suggest the relationship between the birth and muscle strength, pelvic floor mobility and the development of changes such as urinary and fecal incontinence. Manuscript 2 aimed to evaluate the perineal strength and pelvic mobility of primiparous women and to report them to characteristics of gestation and the way of delivery. The sample consisted of twenty-four primiparous women, over 18 years of age, who underwent cesarean delivery or normal delivery with and without episiotomy or forceps and were evaluated in the period from three to six months after gestation. The evaluations were done through evaluation form, perineometry and flexion test sitting and standing. The evaluation of muscle strength, time of contraction and pelvic mobility and their relationship with gestational and clinical variables showed that the women presented a reduction in strength and time of contraction and alteration of pelvic mobility, regardless of the way of delivery; that some clinical and gestational characteristics seem to be related to the pelvic floor musculature and pelvic mobility. It was concluded that there was a reduction in strength and time of contraction and alteration of pelvic mobility, regardless of the way of delivery. In general, some clinical and gestational characteristics seem to influence pelvic strength and mobility. Thus, early evaluation to more accurately identify the repercussions of such pathways may avoid pelvic symptoms. The product generated from the dissertation was a folder entitled: Natural Childbirth, Cesarean Delivery, repercussions on the organism, containing information pertinent to possible changes from gestation and delivery, training for perineal strengthening and postural care for prophylaxis of complications generated during childbirth, as well the puerperium.